2016
DOI: 10.1165/rcmb.2016-0091oc
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Monocyte-Activating Polypeptide II Mediates Macrophage Migration in the Development of Hyperoxia-Induced Lung Disease of Prematurity

Abstract: Myeloid cells are key factors in the progression of bronchopulmonary dysplasia (BPD) pathogenesis. Endothelial monocyte-activating polypeptide II (EMAP II) mediates myeloid cell trafficking. The origin and physiological mechanism by which EMAP II affects pathogenesis in BPD is unknown. The objective was to determine the functional consequences of elevated EMAP II levels in the pathogenesis of murine BPD and to investigate EMAP II neutralization as a therapeutic strategy. Three neonatal mouse models were used: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
3
17
0
Order By: Relevance
“…Animal harvesting. Overall techniques used in mouse lung harvesting and analysis have previously been published by our groups (16,22,(41)(42)(43). In brief, at P14, lungs were either inflation-fixed at 25 cm H 2 O with 4% paraformaldehyde for paraffin embedding/histology or were snap frozen for protein and RNA isolation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal harvesting. Overall techniques used in mouse lung harvesting and analysis have previously been published by our groups (16,22,(41)(42)(43). In brief, at P14, lungs were either inflation-fixed at 25 cm H 2 O with 4% paraformaldehyde for paraffin embedding/histology or were snap frozen for protein and RNA isolation.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, at P14, lungs were either inflation-fixed at 25 cm H 2 O with 4% paraformaldehyde for paraffin embedding/histology or were snap frozen for protein and RNA isolation. BALF was obtained at P14 as previously described (22,41,42) and was used for exosome and cytokine analyses. All studies were performed with 4-9 animals per group, per condition, in every experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal lung vascular development is also a characteristic pathophysiologic feature of BPD (13), and higher concentrations of endostatin (an angiogenesis inhibitor) have been found in tracheal aspirates of infants with BPD (14,15). Animal studies show that hyperoxia decreases endothelial mitochondrial antioxidant defenses and disrupts pulmonary endothelial tight junctions, leading to arrested pulmonary development (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…At present, it has been found that EMAP-II has many functions on regulating cell function. In the development of hyperoxia-induced lung disease of prematurity, EMAP-II can mediate macrophage migration (Lee et al, 2016 ). EMAP-II is increased in children and adolescents with type I diabetes, which are related to micro-vascular complications (Adly et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%